2017
DOI: 10.1038/s41598-017-08255-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, membrane nanostructure and stiffness for quality assessment of packed red blood cells

Abstract: Transfusion of packed red blood cells (PRBC) to patients in critical states is often accompanied by post-transfusion complications. This may be related with disturbance of properties of PRBC and their membranes during long-term storage in the hemopreservative solution. The purpose of our work is the study of transformation of morphology, membranes stiffness and nanostructure for assessment of PRBC quality, in vitro. By atomic force microscopy we studied the transformation of cell morphology, the appearance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 58 publications
8
33
0
1
Order By: Relevance
“…Indeed, the ATP content is expected to influence strength and dynamics of the interaction between cytoskeleton and plasma membranes, and the roughness measurements allow its quantification. It is also worth noting that similar effects, namely, the appearance of topological defects on the surface over the ageing pattern, have been evidenced in blood exposed to hemin or in long‐term storage conditions . In the present case, because of the different environmental stimulus, the defects shown in Figure can have a quite different molecular origin (eg lesser involvement of Hb and stronger correlation to cytoskeleton degradation).…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, the ATP content is expected to influence strength and dynamics of the interaction between cytoskeleton and plasma membranes, and the roughness measurements allow its quantification. It is also worth noting that similar effects, namely, the appearance of topological defects on the surface over the ageing pattern, have been evidenced in blood exposed to hemin or in long‐term storage conditions . In the present case, because of the different environmental stimulus, the defects shown in Figure can have a quite different molecular origin (eg lesser involvement of Hb and stronger correlation to cytoskeleton degradation).…”
Section: Discussionsupporting
confidence: 69%
“…In our earlier works, we described that irreversible changes in cell shape and changes in the membrane nanosurface of RBCs are associated with distortion of the spectrin matrix. It is suggested that the influences of various pharmaceuticals, long‐term storage of blood, ionizing radiation, and various diseases lead to irreversible changes in the spectrin network …”
Section: Resultsmentioning
confidence: 99%
“…The sedimentation method was used to prepare the RBC monolayer . To do this, 400 μL of RBC suspension were dropped onto glass with polylysine and left for 20 minutes at a temperature of 20°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations